G0W0 plus BSE calculations of quasiparticle band structure and optical properties of nitrogen-doped antimony trisulfide for near infrared optoelectronic and solar cells application - Afiq Radzwan (Tanjung Malim, 2021)
G0W0 plus BSE calculations of quasiparticle band structure and optical properties of nitrogen-doped antimony trisulfide for near infrared optoelectronic and solar cells application by Afiq Radzwan